The Union Action in Wage Dispute In Argentina During the Post-Convertibility Period (2006-2010) - Barrera Insua, Facundo (Sociedad y Economía, 2015)
After all scientific and technical transformations that occurred during the global capita- lism since the mid-seventies, last century, several authors questioned the centrality of labor (and workers' organizations) as a relevant category to study the social conflict and its dynamics. Using statistical analysis based on data from labor conflicts during the period 2006-2010, and building categories of union and non-union action, using statistical analy- sis based on data from labor conflicts for the period 2006-2010, and the construction of categories and nonunion labor action, this paper refutes such argument by proving that union action is not only responsible for the increment in conflict labor in Argentina, but that it also holds it in crucial times like during the collective negotiation such the and workers' vacations, while contributing to the incorporation of a new union organization.